Applied Montology Using Critical Biogeography in the Andes - Sarmiento, Fausto O.; Tomas Ibarra, J.; Barreau, Antonia; Cristobal Pizarro, J.; Rozzi Marin, Ricardo Roberto; Gonzalez, Juan A.; Frolich, Larry M. (My University, 2017)
More than most other landforms, mountains have been at the vanguard of geographical inquiry. Whether promontories, cultural works on slopes, or even metaphorical/spiritual heights, mountain research informs current narratives of global environmental change. We review how montology shifts geographic paradigms via the novel approach of critical biogeography in the Andes. We use it to bridge nature and society through indigenous heritage, local biodiversity conservation narratives, and vernacular nature-culture hybrids of biocultural landscapes (BCLs), focusing on how socioecological systems (SES) enlighten scientific query in the Andes. In our Andean study cases, integrated critical frameworks guide the understanding of BCLs as the product of long-term human-environment interactions. With situated exemplars from place naming, wild edible plants, medicinal plants, sacred trees, foodstuffs, ritualistic plants, and floral and faunal causation, we convey the need for cognition of mountains as BCLs in the Anthropocene. We conclude that applied montology allows for a multi-method approach with the four Cs of critical biogeography, a model that engages forward-looking geographers and interdisciplinary Andeanists in assessments for sustainable development of fragile BCLs in the Andes.
Keywords: andes; biocultural landscape; critical biogeography; ethnobiology; intangible heritage; montology; paramo